UMP will host 2022 Public University Golf Tournament - Mohd Aznorizamin, Ismail (2022)
SHAH ALAM, 8 December 2021 - Universiti Malaysia Pahang (UMP) will be chosen as the host for the 49th Malaysian Public University Golf Tournament ahead of UMP’s 20th Anniversary Celebration next year.